Management of patient with Sturge-Weber syndrome: a case report - Govori, Valbona (BioMed Central, 2009)
INTRODUCTION: Sturge-Weber syndrome sometimes referred to as encephalotrigeminal angiomatosis, is a rare congenital neurological and skin disorder. CASE PRESENTATION: This is case report of a 18-year-old mentally disabled boy, with long-standing seizures, with a port-wine nevi on the left side of the face along the distribution of trigeminal nerve. Interictal encephalogram showed bilateral slow activity, pronounced in the left hemisphere, with epileptogenic activity in the left temporo-parietal region. Skull radiograph, computerized tomography and magnetic resonance imaging showed intracranial calcifications and atrophy of the left brain hemisphere. CONCLUSION: Professional counseling and support in addition to drug treatment can provide help to patients and their family to overcome their problems and improve the treatment outcome.